2018
DOI: 10.1371/journal.pone.0190232
|View full text |Cite
|
Sign up to set email alerts
|

Shifting gears: Diversification, intensification, and effort increases in small-scale fisheries (1950-2010)

Abstract: Locally sustainable resource extraction activities, at times, transform into ecologically detrimental enterprises. Understanding such transitions is a primary challenge for conservation and management of many ecosystems. In marine systems, over-exploitation of small-scale fisheries creates problems such as reduced biodiversity and lower catches. However, long-term documentation of how governance and associated changes in fishing gears may have contributed to such declines is often lacking. Using fisher intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 64 publications
2
24
0
Order By: Relevance
“…When participatory maps of human practices are paired with maps of natural systems, their union can be used to delineate sustainable activities from those that are damaging. In the Danajon Bank, participatory mapping revealed that fishing effort increased more than 1800%, and that this increase was due to the growing number of individuals fishing, rather than to changes in individual fishing effort [5,24]. In contrast, non-spatial measures greatly underestimated the severity of this change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When participatory maps of human practices are paired with maps of natural systems, their union can be used to delineate sustainable activities from those that are damaging. In the Danajon Bank, participatory mapping revealed that fishing effort increased more than 1800%, and that this increase was due to the growing number of individuals fishing, rather than to changes in individual fishing effort [5,24]. In contrast, non-spatial measures greatly underestimated the severity of this change.…”
Section: Discussionmentioning
confidence: 99%
“…Communities in the region maintain a high reliance on marine resources and fishing is a primary livelihood. Fishers employ diverse fishing practices, enabling them to catch a diverse range of marine life [24]. Most fishers use outrigger canoe style boats.…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…These changes include more experience in catching Usipa gained over time by fishers, as well as a change in the fishing grounds. In addition, the gear used to target Usipa has greatly been modified as indicated by one of the respondents that the bunt diameter has been increased by 2 fold and others by 3 fold and that the size of the gear has also been increased by simillar margin as the bunt (Sergrath et al, 2018).…”
Section: Fishing Effortmentioning
confidence: 99%